(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Public-private partnerships (PPPs) have emerged as a promising approach to addressing the complex challenges of sustainable development in rural areas. However, the success of these partnerships’ hinges on the establishment of effective governance models that facilitate collaboration, transparency, and accountability among diverse stakeholders. This paper examines the key elements of robust governance frameworks for rural sustainability PPPs, including clearly defined roles and responsibilities, mechanisms for transparency and information sharing, capacity building and stakeholder engagement, and comprehensive risk management and conflict resolution strategies. The paper explores the contextual factors, resource constraints, and policy and regulatory environments that influence the design and implementation of governance models in rural settings. It highlights the importance of tailoring governance structures to the unique geographic, socio-economic, cultural, and institutional dynamics of rural communities. Additionally, the paper discusses best practices and recommendations for effective governance, such as promoting public-private-community partnerships, leveraging technology and digital tools, and fostering cross-sector collaboration and knowledge sharing. By adopting comprehensive governance models that address the specific challenges and opportunities of rural sustainability projects, PPPs can unlock their full potential to drive transformative economic, social, and environmental impacts.